AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL, METANOL, DAN AQUADES DARI KULIT BUAH MUNDAR (Garcinia forbesii) - Muhammad Ikhwan Rizki; Liling Triyasmono; Khoerul Anwar; Anna Khumaira Sari (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2022)
Mundar (Garcinia forbesii) is a typical plant from South Kalimantan. Mundar pericaps can be used as a natural antioxidant. The use of solvents in the extraction process can affect the antioxidant activity. The purpose of this study was to determine of phytochemical compounds and antioxidant activity of the ethanol, methanol, and aquades extracts from pericaps of mundar (Garcinia forbesii). Mundar pericaps is dried, then made into powder. Mundar pericaps powder was extracted with three different solvents, ethanol 70%, methanol, and aquades. Phytochemical screening and analysis by thin layer chromatography were performed on the three extracts. The three extracts were tested for antioxidant activity by DPPH method. The results showed that ethanol and methanol extracts contained phytochemical compounds of phenolic, flavonoids, tannins, alkaloids, steroids, and terpenoids. Aquades extract contains phenolic, flavonoids, tannins, and alkaloids. The chromatographic profile showed that the ethanol and methanol extracts had an Rf value of 0.307. The antioxidant activity from highest to lowest was ethanol extract (192.64 ppm), methanol extract (236.64 ppm), and aquades extract (443.13 ppm) from mundar pericaps